Powdered Beverage from Native Plants from Argentina (Zuccagnia punctata and Solanum betaceum) Obtained by Spray-Drying: A Promising Source of Antioxidant Compounds - Correa Uriburu, Florencia; Zampini, Iris Catiana; Maldonado, Luis Maria; Gómez Mattson, Milagros; Salvatori, Daniela; Isla, María Inés (MDPI, 2023)
In previous studies, the Argentinean native plants called Zuccagnia punctata (jarilla, pus pus, lata) and Solanum betaceum (chilto, tree tomato) were reported as new natural sources of antioxidant compounds, mainly chalcones, anthocyanins and rosmarinic acid derivates. The present study deals with the production of antioxidant beverages of Z. punctata (Zp) extract and chilto juice with honey as sweetener. A Zp extract and red chilto juice were obtained according to Food Code and characterized. The beverages were formulated by using maltodextrin (MD) with two dextrose equivalents (DE), 10 and 15, and then spray-dried at an inlet air temperature of 130 °C. The physicochemical, microscopical, phytochemical and functional characteristics of the powders were surveyed. The experiments carried out showed good physical properties for both formulations showing high water solubility with adequate features for handling, transport and storage. The chromatic parameters of both powdered beverages indicate orange–pink tones regardless of the wall material used. The total polyphenol and flavonoid content in the beverages were kept after spray-drying (92 and 100%, respectively). The anthocyanins were less stable under drying conditions (yield 58%). Both powdered beverages showed high scavenger capacity on ABTS•+, HO• and H2O2 (SC50 between 3.29 to 41.05 µg GAE/mL) and were able to inhibit xanthine oxidase (XOD) activity (CI50 between 91.35 and 114.43 µg GAE/mL). The beverages were neither toxic nor mutagenic in the concentration range with biological activity. The results obtained in the present work scientifically support the use of the powdered beverages of Argentinean native plants as antioxidant.